2011
DOI: 10.1007/s10722-011-9778-2
|View full text |Cite
|
Sign up to set email alerts
|

Maize (Zea mays L.) from the Saharan oasis: adaptation to temperate areas and agronomic performance

Abstract: Saharan maize had been adapted to extreme conditions and could have developed resistance to different stresses. However, genebanks and breeding collections have poor representation from Saharan germplasm and, particularly, from Algeria. This is a preliminary approach to investigate the adaptation and agronomic performance of a representative sample of Saharan maize. We evaluated open-pollinated Saharan populations along with European and American cultivars during two years in humid and dry Spanish locations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…Contrarily, maize landraces are considered reservoirs of favorable alleles that should be used for broadening the base breeding populations (Wietholter et al, 2008;Prasanna, 2012). However, little information is currently available about maize diversity from North Africa, except for Algerian maize populations (Djemel et al, 2012;Aci et al, 2013). However, little information is currently available about maize diversity from North Africa, except for Algerian maize populations (Djemel et al, 2012;Aci et al, 2013).…”
Section: Heterotic Patterns Among Algerian Us Corn Belt and Europeamentioning
confidence: 99%
See 4 more Smart Citations
“…Contrarily, maize landraces are considered reservoirs of favorable alleles that should be used for broadening the base breeding populations (Wietholter et al, 2008;Prasanna, 2012). However, little information is currently available about maize diversity from North Africa, except for Algerian maize populations (Djemel et al, 2012;Aci et al, 2013). However, little information is currently available about maize diversity from North Africa, except for Algerian maize populations (Djemel et al, 2012;Aci et al, 2013).…”
Section: Heterotic Patterns Among Algerian Us Corn Belt and Europeamentioning
confidence: 99%
“…However, little information is currently available about maize diversity from North Africa, except for Algerian maize populations (Djemel et al, 2012;Aci et al, 2013). Djemel et al (2012) and Aci et al (2013) revealed that Algerian maize exhibits a high degree of phenotypic and genetic diversity and a wide range of adaptation to temperate regions. Weatherwax and Randolph (1955) reported that Saharan maize originated from tropical introductions from Spain during the 16th century and from subsequent introduction from African neighboring countries (Aci et al, 2013).…”
Section: Heterotic Patterns Among Algerian Us Corn Belt and Europeamentioning
confidence: 99%
See 3 more Smart Citations